PHYTOCHEMICAL SCREENING AND EVALUATION OF FREE RADICAL SCAVENGING ACTIVITY OF EXTRACT PREPARED FROM LEAVES OF DIGITALIS PURPUREA - NAINWAL, YOGESH CHANDRA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The present study deals with the phytochemical screening and free radical scavenging activity of leaf extract of Digitalis purpurea. Methods: The phytochemicals from the leaf extract of D. purpurea were extracted qualitatively in methanol and confirmed by performing various chemical tests. The free radical scavenging activity of leaves extract was performed using DPPH method with solvents of different polarity, namely, petroleum ether, ethyl acetate, and methanol. The IC50 (50 % inhibition of DPPH) value of free radical scavenging activity of leaf extract was calculated from the graph for each solvent. Results: The leaves extract showed presence of various biologically important phytochemicals such as cardiac glycosides, flavonoids, saponins, anthraquinone, carbohydrates, steroids, phenolic compounds, and aminoacids. The IC50 value of DPPH free radical scavenging activity in petroleum ether, ethyl acetate, and methanolic extract of leaves was found 0.982±0.009 mg/mL, 0.538±0.006 mg/mL and 0.480±0.01 mg/mL respectively. Conclusion: The present study reveals that D. purpurea is medicinally important plant and it can be well exploited for making a diverse range of pharmaceutical drugs. The present investigations also give an insight to scientists and researchers to come up with innovative ideas for effective eradication of different diseases.